A case of retroperitoneal lymphangioma in an adult - Cong Thao Trinh; Nhu Tung Tran; Bich Thuy Thi Vo; Hoang Anh Thi Van; Van Trung Hoang; Minh Duc Nguyen (Elsevier, 2021)
Retroperitoneal lymphangiomas are uncommon lymphatic malformations that present as cystic masses, arise from isolated lymphatic vessels, and do not communicate with the normal lymphatic system. We report a rare case of retroperitoneal lymphangioma in a young man who presented with abdominal pain and diarrhea. The patient was successfully treated with tumor resection, and lymphangioma was confirmed by histopathological analysis. In addition to describing this case, we present a review of the clinical manifestations, pathological findings, radiological findings, and treatments associated with retroperitoneal lymphangioma.